Self-hypnosis: a gateway to personal transformation / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2024)
Hypnosis is a psychological state in which individuals experience a trance-like state to access their subconscious mind. Contrary to popular belief, hypnotherapy does not involve mind control or being in a state of unconsciousness. Instead, it induces a state of focused attention and increased awareness like deep meditation or concentration. Individuals remain aware, in control of their actions and cannot be forced to act against their own will. Research has recognized the therapeutic effect of hypnotherapy in enhancing cognitive and emotional processes by employing the power of suggestion and mental imagery (Kihlstrom, 2008; Lynn & Green, 2011). In a way, it offers a unique pathway towards an individual’s healing and self- improvement.